2020
DOI: 10.11648/j.ajns.20200904.28
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Using Breathing Exercise on Sleep Quality Among Hospitalized Patients

Abstract: Sleep disturbance among hospitalized patients has many factors especially at critical care units. Daily breathing exercises as pursed lip breathing (PLB) and diaphragmatic breathing improves sleep quality and reduces the occurrence of delirium. Aim of the study Evaluate the effectiveness of using breathing exercise on sleep quality among hospitalized patients. Design quasi experimental design. Sample A purposive sample including 152 patients were divided into four equal groups two from the Medical ward (study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…According to the results of the current study, boys made up more than half of the children. These results are corroborated by Abd El Khalik et al, (2020), who investigated "The Effectiveness of Using Breathing Exercise on Sleep Quality among Hospitalized Patients" and found that men made up the majority of the study groups.…”
Section: Discussionsupporting
confidence: 53%
“…According to the results of the current study, boys made up more than half of the children. These results are corroborated by Abd El Khalik et al, (2020), who investigated "The Effectiveness of Using Breathing Exercise on Sleep Quality among Hospitalized Patients" and found that men made up the majority of the study groups.…”
Section: Discussionsupporting
confidence: 53%
“…The significant improvement in the control group in this study could be associated with the physiological outcomes of the breathing exercise and Benson relaxation technique. This explanation was confirmed with Abd El Khalik et al [16] who found that breathing exercise practice influences bodily functions, brain activity, and autonomic nervous system balance, thus it represents a prime method for inducing relaxation and improving sleep quality.…”
Section: Between Group Comparisonsupporting
confidence: 56%
“…Another study found that deep breathing exercises increase postoperative sleep quality (Abd El Khalik et al, 2020;Alkan et al, 2017). Also, breathing exercises performed before sleeping can increase sleep quality (Tsai et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Ghorbani et al (2018) found deep breathing exercises prevent postoperative decreases in sleep quality (Ghorbani et al, 2018). Another study found that deep breathing exercises increase postoperative sleep quality (Abd El Khalik et al, 2020; Alkan et al, 2017). Also, breathing exercises performed before sleeping can increase sleep quality (Tsai et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation